Representasi Humanisme dalam Lirik Lagu Perahu Kertas (Sebuah Kajian Semiotik Roland Barthes) - Afifah Chairunnisa; Silvia Rosa (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
Songs serve as mirrors reflecting the cultural and philosophical values of their societies. This journal examines how humanism is represented in "Perahu Kertas," analyzed through Roland Barthes' symmetrical approach and descriptive qualitative methods. Focusing on the song’s lyrics and relevant literature, the study uncovers that "Perahu Kertas" embeds humanistic myths within its symbolic language. Symbols such as paper boats, handwritten letters, the personal pronouns “you” and “I,” and radar are not only literal elements but also carry deeper connotations. These symbols collectively evoke themes of personal journey, interpersonal relationships, and the quest for existential meaning. At the denotative level, a paper boat may symbolize a simple vessel or a childhood memory, while at the connotative level, it represents the journey of self-discovery and the forging of connections between individuals and communities. The repeated use of “you” and “I” emphasizes subjectivity and mutual recognition, essential traits of humanistic thought. Radar, as a motif, underscores the act of searching and navigating life’s uncertainties. Through the denotative and connotative analysis, it becomes clear that the myth of humanism is woven throughout "Perahu Kertas," illustrating how popular music can articulate collective aspirations and philosophical ideals. This analysis demonstrates the enduring relevance of humanistic values in contemporary cultural expressions